Um estudo de alternativas de financiamento da pós-graduação strictu sensu: uma análise da Engenharia de Produção - Nunes, Camila Felin (2013)
Brazil has shown a significant increase in the last decade, in the number of masters and doctors, trained in federal and state institutions of higher education. However, this effort creates budget pressures to support investments in high-level education in the country, and to maintain the quality of the courses need a consistent supply of resources, in order to provide better conditions for the provision of those courses. In this sense, has become a clear need to diversify and stabilize funding sources for these training activities become sustainable, as they present results in favor of the competitive capacity of domestic industries. In this context, a postgraduate in Production Engineering is of great importance to the nation, for its potential to enhance improvements in quality and productivity of Brazilian industry. This work investigates alternative funding postgraduate strictu sensu in PPGEP-UFSM starting from the knowledge of the financing models for postgraduate courses in Germany, and the calculation of market profile of local and regional industries. Therefore, make use of the documentary research technique, with data management of the Federation of Industries of the State of Rio Grande do Sul. To adopt a funding model of postgraduate similar to that practiced in Germany, where universities and industry are partners in the development of technologies and innovations, it is recommended that the PPGEP-UFSM seek greater affinity between its research and production activities regional industries. For this purpose, it is suggested that the research program to develop compatible with the machinery produced in the region of technologies for the production of food production, and also for improving the handling and processing of meat and grain, allowing an improvement to local industries of competitiveness. Keywords: Postgraduate. Financing graduate. Industrial Engineering